Pengaruh Pertumbuhan Penjualan, Profitabilitas, Likuiditas dan Kebijakan Dividen Terhadap Nilai Perusahaan pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2015-2017 - Elyda Crisna Tamba; Lasmian Pandiangan; Riva Novia Ginting; Wilsa Road Betterment Sitepu (Owner : Riset dan Jurnal Akuntansi, 2020)
This study intends to check the impact of sales growth, profitability, liquidity, and dividend policy on firm value on manufacturing companies listed on the IDX. The sample of 36 research companies listed on the Indonesia Stock Exchange 2015-2017. The independent variable is sales growth, profitability, liquidity, dividend policy. While the dependent variable is firm value. The way to choose samples is purposive sampling. Analysis of data with multiple linear regression, the results of this study prove that sales growth partially has no impact and is not significant to the value of the company with a significant amount of 0.176. Profitability is partially positive and significant impact on the value of the company with a significant amount of 0,000. Liquidity partially has no impact and is not significant in firm value with a significant amount of 0.108. Dividend policy is partially positive and significant impact on the value of the company with a significant amount of 0,000